2019
DOI: 10.3324/haematol.2019.216457
|View full text |Cite
|
Sign up to set email alerts
|

Molecular minimal residual disease negativity and decreased stem cell mobilization potential predict excellent outcome after autologous transplant in NPM1 mutant acute myeloid leukemia

Abstract: Molecular minimal residual disease negativity and decreased stem cell mobilization potential predict excellent outcome after autologous transplant in NPM1 mutant acute myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Autologous transplantation can potentially allow a selected group of patients, especially with low and potentially intermediate genetic risk, to avoid over-treatment with allogeneic transplantation, providing 50–60% probability of long-term LFS [74]. The recently published excellent outcomes of autologous transplantation in MRD negative patients with low or intermediate genetic risk [75,76,77,78] prompt re-evaluating the role of autologous transplantation in AML. In this regard, a group from China compared retrospectively autologous to allogeneic HSCT in AML patients with favorable or intermediate genetic risk [76].…”
Section: The Role Of Mrd In Hsct For Amlmentioning
confidence: 99%
“…Autologous transplantation can potentially allow a selected group of patients, especially with low and potentially intermediate genetic risk, to avoid over-treatment with allogeneic transplantation, providing 50–60% probability of long-term LFS [74]. The recently published excellent outcomes of autologous transplantation in MRD negative patients with low or intermediate genetic risk [75,76,77,78] prompt re-evaluating the role of autologous transplantation in AML. In this regard, a group from China compared retrospectively autologous to allogeneic HSCT in AML patients with favorable or intermediate genetic risk [76].…”
Section: The Role Of Mrd In Hsct For Amlmentioning
confidence: 99%
“…The stratification of patients for these consolidation treatment options relies on the genetic risk assessed by cytogenetics and molecular analyses at initial diagnosis, the response to induction treatment, and the morbidity and mortality associated with the treatment options [1,2]. The concept of minimal or measurable residual disease (MRD) after induction has a significant impact on the type of consolidation and, increasingly, maintenance treatment [3]. MRD is defined as the detection of malignant cells at a submicroscopic level, and it has been shown to be an independent prognostic factor for the risk of relapse and death [4].…”
Section: Introductionmentioning
confidence: 99%
“…Multiparameter flow cytometry as well as molecular methods are routinely used for diagnosis and screening for residual disease in AML patients. While recurrent mutations in genes such as FLT3 or NPM1 have been incorporated in risk assessment for a long time [1,3], the introduction of next-generation sequencing (NGS) into the hematologic routine has enabled the discovery of a multitude of additional and often novel mutations [5]. The detection of druggable mutations has also opened the door for customized treatment strategies, some of which were integrated in the European LeukemiaNet (ELN) risk assessment and treatment for patients with AML [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated that autologous HCT performed in CR1 has a low non-relapse mortality (NRM) and is associated with a lower relapse rate than consolidation chemotherapy alone [ 3 7 ]. Durable responses following autologous HCT have been reported within distinct AML subtypes including core binding factor or NPM1 -mutated AML [ 8 , 9 ]. Allogeneic HCT is the preferred option in patients with adverse risk profiles, as the graft-versus-leukemia (GvL) effect [ 10 , 11 ] cannot be provided by HDCT/autologous HCT outweighing in these patients the risks of graft-versus-host disease (GvHD).…”
Section: Introductionmentioning
confidence: 99%